XueFu ZhuYu Decoction Alleviates Cardiopulmonary Bypass-Induced NLRP3 Inflammasome-Dependent Pyroptosis by Inhibiting IkB-α/NF-κB Pathway in Acute Lung Injury Rats. (10th September 2022) - Li, Hui; Zhang, Wenlei; Lou, Qiaoqin; Chang, Yuejin; Lin, Zhenhao; Lou, Lingli
Abstract : XueFu ZhuYu Decoction (XFZYD) is an effective prescription that is widely used to improve blood circulation by removing blood stasis. This study aimed to investigate the effects and the underlying molecular mechanisms of XFZYD on lung pyroptosis in cardiopulmonary bypass- (CPB-) induced acute lung injury (ALI) rats. A rat model of ALI was induced by CPB treatment after XFZYD, Ac-YVAD-CMK, and Bay-11-7082 administration. The respiratory index (RI) and oxygenation index (OI) were determined at each time point. The levels of interleukin (IL)-1 β, IL-6, IL-18, and TNF- α in serum and lung were measured by enzyme-linked immunosorbent assays (ELISA). Moreover, the protein levels, neutrophil counts, and total cell of bronchoalveolar lavage fluid (BALF) were detected. Additionally, Myeloperoxidase (MPO) expression was detected by immunohistochemical assay. Lung injury was evaluated with the wet/dry (W/D) ratio and pathologic changes, respectively. Besides, the expression of NLRP3 inflammasome and IkB- α /NF- κ B pathway proteins was estimated by immunofluorescence, quantitative real-time PCR (qRT-PCR), and Western blotting assays, respectively. XFZYD pretreatment significantly ameliorated pulmonary ventilation function and reduced the CPB-induced lung histopathological injury, inflammatory cell infiltration in BALF and lung, and the apoptosis of lung cells. Interestingly, XFZYD decreased the CPB-induced NLRP3, ASC, Caspase-1 p20, Pro-GSDMD, GSDMD p30, IL-18, IL-1 β p-P65, and p-IKB α mRNA or protein levels in lung tissues in ALI model rats. In summary, these findings suggest that XFZYD effectively mitigates NLRP3 inflammasome-dependent pyroptosis in CPB-induced ALI model rats, possibly by inhibiting the IkB- α /NF- κ B pathway in the lung.